2022
DOI: 10.1002/jad.12033
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual associations between active social media use, exhaustion, and bedtime vary according to age—A longitudinal study across adolescence

Abstract: Introduction:The majority of adolescents engage with others online, and using social media is one of their top activities. However, there is little longitudinal evidence addressing whether active social media use is associated with study-related emotional exhaustion or delayed bedtime at the individual level of development during adolescence. Method: A 6-year longitudinal survey study (N = 426, female, 65.7%) was conducted (2014)(2015)(2016)(2017)(2018)(2019) in Finland when the participants were 13-19 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…The association between out-of-school social media use (time spent on social media sites posting or browsing content) and school connectedness varied by age, showing a stronger association in students in grade 12 compared to students in grade 7 (Sampasa-Kanyinga et al, 2019). In line with and in addition to Sampasa-Kanyinga and colleagues (2019), Maksniemi and colleagues (2022) found (in a Finnish sample) that the longitudinal intra-individual associations between digital engagement and academic well-being varied across adolescence: social media use was not associated with school-related exhaustion in early adolescence, but a positive association was found in middle and late adolescence.…”
Section: The Effects Of Digital Engagement On Academic Functioningmentioning
confidence: 63%
“…The association between out-of-school social media use (time spent on social media sites posting or browsing content) and school connectedness varied by age, showing a stronger association in students in grade 12 compared to students in grade 7 (Sampasa-Kanyinga et al, 2019). In line with and in addition to Sampasa-Kanyinga and colleagues (2019), Maksniemi and colleagues (2022) found (in a Finnish sample) that the longitudinal intra-individual associations between digital engagement and academic well-being varied across adolescence: social media use was not associated with school-related exhaustion in early adolescence, but a positive association was found in middle and late adolescence.…”
Section: The Effects Of Digital Engagement On Academic Functioningmentioning
confidence: 63%
“…In our view, the proposed measure is particularly useful for future research because of several reasons: First, using the DIMI researchers could detect differences in digital maturity relating to specific dimensions with the DIMI and develop tailored interventions to reduce such differences. Second, the DIMI enables researchers to study the development of individual dimensions which do not necessarily change in parallel and may vary according to the individual level of development during adolescence (Maksniemi et al, 2022). And third, the multi-facetted approach of the DIMI allows the further advancement of existing theories that combine positive psychology and technology use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the duration and timing of SMU also have significant implications for sleep and mental health, as excessive or inappropriate use of social media at certain timing, for example at bedtime, can potentially contribute to negative biopsychosocial effects. The Socio-Digital Participation Inventory includes four items to measure the frequency of SMU on a seven-point frequency scale (1 = never, 2 = a couple of times a year, 3 = monthly, 4 = weekly, 5 = daily, 6 = multiple times a day, 7 = all the time) [ 25 •]. The total time spent on SMU (in daytime and night-time) are usually captured by questionnaires and social media time use diary [ 38 •].…”
Section: Overview Of Smumentioning
confidence: 99%
“…In addition, adolescents with evening chronotype preference and shorter sleep duration were found to have longer usage of social media, suggesting a potential bidirectional relationship between SMU and sleep duration [ 54 ]. Another cohort study conducted by Maksniemi and colleagues did not find a significant association between SMU and bedtime among 426 youth aged between 13 and 19 [ 25 •]. Interestingly, subgroup analyses indicated that significant associations were only observed in early adolescence (at age 13 and 14), but not in middle (at age 14 and 15) nor late adolescence (at age 17 and 18) [ 25 •].…”
Section: Synthesis Of Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation